Care centered on patients and family members in intensive care (Research, Society and Development, 2020)
Objective: To analyze the scientific productions on care aimed at maintaining the family bond in the care process for patients in the intensive care unit. Method: This is an integrative bibliographic review carried out through access to the Scientific Electronic Electronic Library Online (SciElo) and Latin American and Caribbean Literature in Health Sciences (Lilacs) databases, studies in Portuguese were included. , which addressed the proposed theme published between 2009 and 2018. Results: Eleven studies were included. Reflection on the theme allows us to infer that it is necessary to offer health services that meet the demands of listening, touch and sensitivity together with scientific knowledge, promoting the well-being of inpatients in intensive care units. Final considerations: The analysis allows us to infer that the interpersonal relationships existing between the family and the patient can assist in the process of evolution and clinical improvement of the patient in the intensive care unit.